Pembuatan Iklan Game Berbasis Instagram - Agnes Renica Irwan; Riwinoto Riwinoto (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
Current developments have made online media or social media a platform that is widely used and in demand, and there have been many uses of social media such as Instagram for advertising or promotion. To promote products, among others, game ads "Bisa Jadi" are products that will be advertised on the Instagram social media platform in the form of video game ads. The game "Bisa Jadi" is a puzzle game where the player aims to guess the instructions and rules of the game. And the main purpose of making this game ad is to introduce or promote games made by the Indonesian Float Game company. Instagram is considered the right place to promote products in the form of advertisements and Instagram-based game ads. In Instagram there are also various kinds of features, and the features used in advertising the “Bisa Jadi” game use the Instagram Story.